The Routledge handbook of gender and development - Coles, Anne; Gray, Leslie; Momsen, Janet Henshall (Routledge, Tayloe & Francis Group, 2015)
"The Routledge Handbook of Gender and Development provides a comprehensive statement and reference point for gender and development policy making and practice in an international and multi-disciplinary context. Specifically, it provides critical reviews and appraisals of the current state of gender and development and considers future trends. It includes theoretical and practical approaches as well as empirical studies. The international reach and scope of the Handbook and the contributors' experiences allow engagement with and reflection upon these bridging and linking themes, as well as the an examination of the politics and policy of how we think about and practice gender and development. Organized into eight inter-related sections, the Handbook contains over 50 contributions from leading scholars, looking at conceptual and theoretical approaches, environmental resources, poverty and families, women and health related services, migration and mobility, the effect of civil and international conflict, and international economies and development. This Handbook provides a wealth of interdisciplinary information and will appeal to students and practitioners in Geography, Development Studies, Gender Studies and related disciplines"--